Helping Teens Answer the Question "Who Am I?": Sexual Development in Adolescents - Rosemary V. Barnett; Sally A. Moore (EDIS)
FCS-2296, a 3-page fact sheet by Rosemary V. Barnett and Sally A. Moore, is the fifth of a series that explores adolescence in terms of physical, cognitive, social, moral, gender, and sexual development. This publication focuses on the sexual development that adolescents experience. Includes references. Published by the UF Department of Family Youth and Community Sciences, March 2009.